Chemoprophylaxis for the prevention of tuberculosis in kidney transplant recipients: A systematic review and meta-analysis - Yuan, Zhihui; Chao, Sheng; Xu, Yuan; Niu, Yulin (Frontiers in Pharmacology, 2023)
Background: A systematic review and meta-analysis was performed to investigate the efficacy and safety of isoniazid (INH) prophylaxis to prevent tuberculosis (TB) infection in kidney transplant recipients (KTRs). Methods: Web of Science, SCOPUS, and PubMed were searched to identify relevant studies that compared the effects among patients who received INH prophylaxis after transplantation. Results: A total of 13 studies (involving 6,547 KTRs) were included in our analysis. We found that the risk of active TB infection (RR: 0.35, 95%CI 0.27–0.45, p < 0.01) for KTRs was lower in the INH treatment group than in those without prophylaxis. However, there was no significant difference between the two groups in mortality (RR: 0.93, 95%CI 0.67–1.28, p = 0.64), acute rejection (RR: 0.82, 95%CI 0.44–1.51, p = 0.52), and hepatotoxicity (RR: 1.25, 95%CI 0.94–1.65, p = 0.12). Conclusion: Isoniazid prophylaxis is a safe and effective for KTRs on reactivation of latent TB infection.